Absence of Circadian Rhythms of Preterm Premature Rupture of Membranes and Preterm Placental Abruption - Luque-Fernandez, Miguel Angel (Ann Epidemiol, 2014)
PURPOSE: Data regarding circadian rhythm in the onset of spontaneous preterm premature rupture of membranes (PROM) and placental abruption (PA) cases are conflicting. We modeled the time of onset of preterm PROM and PA cases and examined if the circadian profiles varied based on the gestational age at delivery. METHODS: We used parametric and nonparametric methods, including trigonometric regression in the framework of generalized linear models, to test the presence of circadian rhythms in the time of onset of preterm PROM and PA cases, among 395 women who delivered a singleton between 2009 and 2010 in Lima, Peru. RESULTS: We found a diurnal circadian pattern, with a morning peak at 07h:32’ (95%CI:05h:46’ – 09h:18’) among moderate preterm PROM cases (P-value<0.001), and some evidence of a diurnal circadian periodicity among PA cases in term infants (P-value=0.067). However, we did not find evidence of circadian rhythms in the time of onset of extremely or very preterm PROM (P-value=0.259) and preterm PA (P-value=0.224). CONCLUSIONS: The circadian rhythms of the time of onset of preterm PROM and PA cases varied based on gestational weeks at delivery. While circadian rhythms were presented among moderate preterm PROM and term PA cases, there was no evidence of circadian rhythms among preterm PA and very or extremely preterm PROM cases, underlying other mechanisms associated with the time of onset.